Jekel’s Epidemiology, Biostatistics, Preventive Medicine, and Public Health, Edition: 4 - David, L. Katz (Elsevier, 2021)
Jekel's Epidemiology, Biostatistics, Preventive Medicine, and Public Health is the only textbook that combines the disciplines of medical epidemiology, biostatistics, preventive medicine, and public health in one convenient resource. Written by renowned epidemiologists and public health experts, this text presents the information you need with a clinical focus, using real-life medical examples throughout